An interpenetrating network poly(diethylene glycol carbonate)-based polymer electrolyte for solid state lithium batteries. Issue 22 (23rd May 2017) - Liu, Xiaochen; Ding, Guoliang; Zhou, Xinhong; Li, Shizhen; He, Weisheng; Chai, Jingchao; Pang, Chunguang; Liu, Zhihong; Cui, Guanglei
Abstract : A novel polycarbonate-based polymer electrolytes could be applied for high voltage lithium batteries duo to its good electrochemical stability, superior electrochemical performance and molecular structure. Abstract : Polycarbonate-based polymer electrolytes possess superior ionic conductivity at room temperature, higher lithium ion transference number and wider electrochemical stability window when compared with conventional poly(ethylene oxide)-based polymer electrolytes. Herein, the poly(diethylene glycol carbonate) dimethacrylate macromonomer (PDEC-DMA) was synthesized and the resultant interpenetrating network IPN-PDEC polymer electrolyte was developed via free radical in situ polymerization for polymer electrolyte Li metal batteries. This IPN-PDEC polymer electrolyte exhibited a decent ionic conductivity of 1.64 × 10 −4 S cm −1 at room temperature and a wide electrochemical stability window (up to 4.5 V vs. Li + /Li). The LiFePO4 /IPN-PDEC/Li and LiFe0.2 Mn0.8 PO4 /IPN-PDEC/Li cells delivered excellent rate capability and cycling performance at room temperature. An all solid state lithium battery was also demonstrated by applying the as-prepared solid polymer electrolyte (SPE-PDEC) at a temperature of 100 °C, which displayed a superior cycling performance. Therefore, the IPN-PDEC network is a promising polymer electrolyte for solid state lithium batteries.